2014
DOI: 10.1016/j.rgmxen.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori vacA and cagA genotype diversity and interferon gamma expression in patients with chronic gastritis and patients with gastric cancer

Abstract: Background: Helicobacter pylori (H. pylori) is the main risk factor for the development of chronic gastritis, gastric ulcer, and gastric cancer. In H. pylori-infected individuals, the clinical result is dependent on various factors, among which are bacterial components, the immune response, and environmental influence. Aims: To compare IFN-␥ expression with the H. pylori vacA and cagA genotypes in patients with chronic gastritis and patients with gastric cancer. Methods: Ninety-five patients diagnosed with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition, a decreased diversity in the individual human microbiome has been associated to higher probabilities of developing an array of diseases, including obesity and diabetes (17, 85, 86). However, only some Helicobacter strains carry virulence genes, commonly associated to the acquisition of pathogenicity islands, including disease-linked genes, such as CagA and VacA which encode for cytotoxins (55, 8789). …”
Section: Potential Pathogens or Ancient Symbionts?mentioning
confidence: 99%
“…In addition, a decreased diversity in the individual human microbiome has been associated to higher probabilities of developing an array of diseases, including obesity and diabetes (17, 85, 86). However, only some Helicobacter strains carry virulence genes, commonly associated to the acquisition of pathogenicity islands, including disease-linked genes, such as CagA and VacA which encode for cytotoxins (55, 8789). …”
Section: Potential Pathogens or Ancient Symbionts?mentioning
confidence: 99%
“…Increased gastric VacA expression during H. pylori infection is associated with inflammation and premalignant pathology (Sinnett et al, 2016). IFN-γ expression in gastric biopsies varies depending on the H. pylori vacA and cagA genotype (Martinez-Carrillo et al, 2014). In particular, H. pylori infection promotes the Th17 immune response through the virulence factor CagA (Lina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the most frequent genotype was vacA s1m1/cagA+, in both the antrum and corpus. Other studies performed in southern Mexico reported 71.1% and 69.7% [ 30 , 31 ]; furthermore, by gastric pathology, the prevalence of this genotype was 70.7% in chronic gastritis, 57.9% in gastric ulcers, and 81.3% in gastric cancer [ 32 ]. These findings suggest that the vacA s1m1/cagA+ genotype predominates in the Mexican population.…”
Section: Discussionmentioning
confidence: 99%